PENGEMBANGAN MEDIA ANIMASI BERBASIS CANVA PADA MATA PELAJARAN BAHASA INDONESIA DI KELAS VI SDN 166321 TEBING TINGGI - Sitepu, Zulhijjah Febriyani; Masta Marselina Sembiring; Halimatussakdiah; Edizal Hatmi; Dody Feliks Pandimun Ambarita; Dila Handayani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to produce valid, practical, and effective Canva-based animation video learning media in Indonesian language subjects on compound sentences in class VI SDN 166321 Tebing Tinggi. This research is Research and Development using a 4D development model consisting of define, design, development, and disseminate. The subjects of this study were 22 class VI students of SDN 166321 Tebing Tinggi. The data analysis technique in this study was qualitative data obtained from interviews, responses, and suggestions from material validators, media, and education practitioners, while quantitative data was obtained from questionnaires given to material experts, media experts, and education practitioners. The results of the study showed that the assessment of validity by material experts obtained a score of 46 (90%) with the criteria of "Very Eligible", and the assessment by media experts obtained a score of 79 (92.94%) with the criteria of "Very Eligible". Furthermore, the assessment of practicality by grade VI teachers obtained a score of 69 (92%) with the category of "Very Practical". The results of the assessment of effectiveness by grade VI students showed an increase as evidenced by the pre-test results obtaining 43.1% and the post-test results obtaining a score of 82.27%. Based on the effectiveness of the use of Canva-based animated videos using N-Gain, it obtained the criteria of "Effective" with a percentage of 86%. It can be concluded that this research and development produces a product in the form of a valid, practical, and effective Canva-based animated video used in the learning process in grade VI of SDN 166321 Tebing Tinggi.